The Impact of Pulang Balee Marriage on Household Life in Darussalam District, Aceh Besar Regency: Dampak Perkawinan Pulang Balee Dalam Kehidupan Rumah Tangga Di Kecamatan Darussalam Kabupaten Aceh Besar - M. Jakfar, Tarmizi; Achyar, Gamal; Safira, Ridha (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2021)
The contract is carried out consciously by a man and a woman, which is basically with the liking and willingness of both parties. Pleasure and willingness in a marriage is very necessary for the continuity of the household so that the marriage runs with mutual love and love with the aim of fostering a household that is sakinah, mawaddah and rahmah and with the willingness of both parties will also get ridha from Allah SWT. But there is a marriage that is very helpful and gives very good wisdom in marriage. Like the marriage of Pulang Balee, namely marrying his own brother-in-law, whether biological, step-by-step, still related by blood, or his own relatives. However, many of them do not want to and are forced to do it so that it has an impact on their domestic life. Thus, the researchers wanted to examine the problems related to how the practice of Pulang balee marriage in Darussalam District, Aceh Besar District, and how the factors and impacts of Pulang balee marriage in Darussalam District, Aceh Besar District. The research methodology that the author uses is using qualitative research in the form of interviews, observations and documentation. Based on the research that researchers found, the practice of balee return marriage in Darussalam sub-district is the same as usual marriage, starting from the proposal stage and the marriage stage and some of them hold walimah and some do not. The main factor of balee return marriage is thinking about the fate of their child, namely to ensure the care and needs of a child, because the child will be closer to the mother's family. And the impact of the balee return marriage is a positive impact, namely the maintenance of good relations between the two families, being able to look after and raise children together and obtain in-line offspring, as well as maintaining joint property. The negative impact of balee return marriage is a lot of talk from neighbors, feeling awkward at the beginning of marriage, easy to fight and divorce quickly.